Large Cities Fall Behind in “Neighborhood Biodiversity” - Cooper, Daniel S.; Wood, Eric M.; Katz, Nurit D.; Superfisky, Kat; Osborn, Fiona M.; Novoselov, Anna; Tarczynski, Jo; Bacasen, Lara K. (Frontiers in Conservation Science, 2021)
Urbanization is a major driver of global species loss. While cities with suitable habitats and conservation policies may support locally-high biodiversity levels, we suspected that the complexity of managing very large cities might counteract the advantage of large geographic area, and these cities may be less effective at biodiversity conservation. To answer this, we examined the relationship between the number of native indicator wildlife species (mean and maximum) in 112 cities across three metropolitan areas in California (Los Angeles, San Diego, San Jose), metrics related to scale and environmental variables. We found that indicator species richness is positively related to area, income (the luxury effect), and pervious cover - including trees, shrubs and grasses. Despite having a high maximum number of indicator species within their boundaries, the largest cities in our study, Los Angeles, San Jose, San Diego, do a relatively poor job compared with smaller cities at distributing native biodiversity throughout neighborhoods, as measured by their mean species richness. Such variation in “neighborhood biodiversity” may exacerbate existing inequities in residents’ access to nature. Using Los Angeles County as a case study, we compared biodiversity management within the County’s 88 cities of various sizes and characteristics. We ranked General Plan wording in terms of references to biodiversity and conservation and created a management metric. We found that municipalities of various sizes that had high management scores generally had high indicator species richness. This suggests that robust policies may be able to overcome the challenges posed by city size and population.